Toxicity and pathophysiology of palytoxin congeners after intraperitoneal and aerosol administration in rats. (August 2018) - Poli, Mark; Ruiz-Olvera, Patricia; Nalca, Aysegul; Ruiz, Sara; Livingston, Virginia; Frick, Ondraya; Dyer, David; Schellhase, Christopher; Raymond, Jolynne; Kulis, David; Anderson, Donald; McGrath, Sara; et al.
Abstract: Preparations of palytoxin (PLTX, derived from Japanese Palythoa tuberculosa ) and the congeners 42-OH-PLTX (from Hawaiian P. toxica ) and ovatoxin-a (isolated from a Japanese strain of Ostreopsis ovata ), as well as a 50:50 mixture of PLTX and 42-OH-PLTX derived from Hawaiian P. tuberculosa were characterized as to their concentration, composition, in-vitro potency and interaction with an anti-PLTX monoclonal antibody (mAb), after which they were evaluated for lethality and tissue histopathology after intraperitoneal (IP) and aerosol administration to rats. Once each preparation was characterized as to its toxin composition by LC-HRMS and normalized to a total PLTX/OVTX concentration using HPLC-UV, all four preparations showed similar potency towards mouse erythrocytes in the erythrocyte hemolysis assay and interactions with the anti-PLTX mAb. The IP LD50 values derived from these experiments (0.92, 1.93, 1.81 and 3.26 μg/kg, for the 50:50 mix, 42-OH-PLTX, PLTX, and ovatoxin-a, respectively) were consistent with published values, although some differences from the published literature were seen. The aerosol LD50 values (0.063, 0.045, 0.041, and 0.031 μg/kg for the 50:50 mix, 42-OH PLTX, PLTX, and ovatoxin-a, respectively) confirmed the exquisite potency of PLTX suggested by the literature. The tissue histopathology of the different toxin preparations by IP and aerosol administration were similar, albeit with some differences. Most commonly affected tissues were the lungs, liver, heart, salivary glands, and adrenal glands. Despite some differences, these results suggest commonalities in potency and mechanism of action among these PLTX congeners. Highlights: Four preparations of palytoxin congeners were described and characterized by analytical, and in vitro methods. All preparations were administered to rats by IP injection and by inhalation, and lethality and tissue histopathology observed. Histological effects were dose dependent and similar between preparations and routes of administration. The most commonly affected tissues were the lungs, liver, heart, salivary glands and adrenal glands.